Auditoría operativa y su incidencia en la eficiencia de la consultora lt del cantón El Empalme año 2017 - Laaz Torres, Irma Viviana (2018)
The present investigation contemplates important guidelines from the operational audit and focuses on the determination of the efficiency that the LT Tax Consultant generated in the year 2017, one of the main objectives developed in the investigation responds to the development of an operational audit In order to clarify the integral processes applied in the operational services offered in the aforementioned company, one of the relevant problems evidenced in this project is mainly the poor control of the processes that are applied in the services provided , based on this, conceptual, theoretical and legal foundations are established that make possible the sustainability of the topic, for this it is important to establish a mixed research methodology with qualitative quantitative approaches based on methods, techniques, surveys, interviews, work papers, internal control matrix, techniques, procedure and regulations applicable in the country. The processing and analysis was obtained prior to the initial assessments of the processes inherent to the operational audit and its impact on the tax efficiency of the LT consultant, and then proceeded to provide the interpretative analysis of the results to extend the conclusions and recommendations of the the investigation.